2017
DOI: 10.1002/ece3.3679
|View full text |Cite
|
Sign up to set email alerts
|

Phenology largely explains taller grass at successful nests in greater sage‐grouse

Abstract: Much interest lies in the identification of manageable habitat variables that affect key vital rates for species of concern. For ground‐nesting birds, vegetation surrounding the nest may play an important role in mediating nest success by providing concealment from predators. Height of grasses surrounding the nest is thought to be a driver of nest survival in greater sage‐grouse (Centrocercus urophasianus; sage‐grouse), a species that has experienced widespread population declines throughout their range. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
1
24
1
Order By: Relevance
“…In contrast to other recent studies (Gibson et al, ; McConnell et al, ; Ringelman & Skaggs, ; Smith et al, ), we did not find evidence that timing of sampling (projected hatch date vs. failure date) influenced our estimates or inferences regarding the positive association between VOR and nest survival. Most nests were constructed in evergreen shrubs (primarily common juniper, Juniperus communis ); retention of leaves and slow growth of these plants likely prevent appreciable changes in visual obstruction during the incubation period.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other recent studies (Gibson et al, ; McConnell et al, ; Ringelman & Skaggs, ; Smith et al, ), we did not find evidence that timing of sampling (projected hatch date vs. failure date) influenced our estimates or inferences regarding the positive association between VOR and nest survival. Most nests were constructed in evergreen shrubs (primarily common juniper, Juniperus communis ); retention of leaves and slow growth of these plants likely prevent appreciable changes in visual obstruction during the incubation period.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, measuring vegetation following the termination of incubation (either nest failure or hatch, a method commonly used in nesting studies, Gibson, Blomberg, & Sedinger, ) may result in increased levels of concealment at successful nests simply because plants at successful nests will have, on average, more time to develop and produce cover than plants at failed nests. This sampling issue may overestimate the influence of vegetation on nest survival because of a relationship which is correlative, but not causative: Successful nests may be more concealed because they were sampled later, not because greater concealment lead them to be successful (Borgmann & Conway, ; Burhans & Thompson, ; Gibson et al, ; McConnell, Monroe, Burger, & Martin, ; Ringelman & Skaggs, ; Smith et al, ; Vega Rivera, Montaño, Rappole, & Cerda, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no other lesser prairie‐chicken study has reported this threshold relationship, it is consistent with other grouse studies (Wiebe and Martin , McNew et al ). Similarly, nest survival was maximized between 2.0 and 4.0 dm in a quadratic relationship with 75% visual obstruction where visual obstruction was a better predictor of nest survival than vegetation composition; however, this relationship may be biased high because we sampled nest vegetation within 3 days of assessing nest fate, allowing vegetation to grow taller surrounding successful nests (Gibson et al , Smith et al ). Our findings are consistent with those from greater prairie‐chicken ( T. cupido ) research; however, greater prairie‐chicken peak nest survival occurred at a greater visual obstruction, likely because of greater vegetation growth resulting from increased precipitation relative to lesser prairie‐chicken range (McNew et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, measuring vegetation at each nest on its fate date (depredation or hatching) may also be misleading, because vegetation at hatched nests developed over the full period of the nesting cycle, whereas vegetation at depredated nests was measured at an earlier point in the cycle. Critically, as several researchers have recently pointed out, measuring vegetation on the fate date can automatically lead to the erroneous conclusion that taller/denser vegetation is associated with higher nest survival when no effect is actually present (Borgmann & Conway, 2015;Gibson, Blomberg, & Sedinger, 2016;McConnell, Monroe, Burger, & Martin, 2017;Smith et al, 2018). Gibson et al (2016) and McConnell et al (2017) published concurrent and independent studies demonstrating that measuring vegetation at nests on their fate date leads to inflated estimates of the importance of vegetation on nest survival (Figure 2a).…”
Section: Introductionmentioning
confidence: 99%